In situ grown cobalt selenide/graphene nanocomposite counter electrodes for enhanced dye-sensitized solar cell performance. Issue 28 (4th July 2017) - Murugadoss, Vignesh; Wang, Ning; Tadakamalla, Sruthi; Wang, Bin; Guo, Zhanhu; Angaiah, Subramania
Abstract : In situ hydrothermally grown hybrid CoSe/graphene nanocomposites exhibited a higher reaction kinetic rate for tri-iodide reduction and 20% improvement in power conversion efficiency than the Pt counter electrode. Abstract : Graphene nanocomposites were prepared by in situ hydrothermally growing CoSe nanoparticles on different amounts of graphene nanosheets (GNs). The influence of graphene content on the physical and electrochemical properties of CoSe was studied. The CoSe nanoparticles with high catalytic activity accelerated the reduction of triiodide, while the graphene facilitated charge transport during the catalytic process. The CoSe/GN0.50 displayed the highest catalytic activity due to its lowest charge transfer resistance. With increasing the graphene content beyond the optimum concentration, restacking of graphene caused a decreased electrocatalytic activity of CoSe/GN nanohybrids. The DSSCs fabricated with CoSe/GN0.50 as the CE exhibited 20% improvement in the photo-conversion efficiency (PCE) with respect to the standard Pt, much higher than using other reported binary metal selenides. This revealed that CoSe/GN0.50 nanohybrids could be used as a promising alternative to platinum counter electrodes for DSSCs.